A preliminary assessment into perceptions of accuracy and utility of the environmental impact assessment screening tool, South Africa - Lambrecht, Michael (Department of Environmental and Geographical Science, 2022)
Screening is an essential stage within the environmental impact assessment (EIA) process. In this stage, the type and scale of the environmental assessment are determined based on the potential environmental impacts of a development. The South African Department of Forestry, Fisheries, and the Environment (DFFE) has implemented a national web-based spatial screening tool which became mandatory when applying for environmental authorisation as of October 2019. The screening tool identifies environmental sensitivities and prescribes the relevant specialist assessments associated with a development footprint. Since the introduction of the screening tool, environmental assessment professionals' (EAProfs') perceptions regarding the functioning of the tool remain undetermined. Therefore, this research project aims to undertake a preliminary assessment of EAProfs' perceptions of the screening tool's accuracy and utility. A mixed-methods approach involving interviews and an online survey was used to collect qualitative and quantitative data from EAProfs, respectively. The research findings reveal mixed perceptions of the screening tool but with some more unequivocal findings. The results suggest EAProfs generally do not believe the screening tool accurately assigns sensitivity ratings for the various biodiversity themes. In terms of utility, the research found that EAProfs hold a neutral opinion meaning they do not believe the screening tool is useful or not useful, as per the survey. The interviews revealed that several EAProfs believe that the screening tool increases the time and costs of the EIA process, adding nuance to the survey results. Based on these findings, a recommended solution to the accuracy issues is to implement a specialist feedback loop. Additionally, better communication from the DFFE on the process of assigning sensitivity ratings could also enhance perceptions. A potential way forward is for the screening tool to adopt a less prescriptive and more voluntary approach, as used by CapeFarmMapper and Ireland's Environmental Sensitivity Mapping Webtool. Lastly, this research opens avenues for further work on how the accuracy and utility of the screening tool can be improved.